2014
DOI: 10.1089/ast.2014.1184
|View full text |Cite
|
Sign up to set email alerts
|

Seed-to-Seed-to-Seed Growth and Development of Arabidopsis in Microgravity

Abstract: Arabidopsis thaliana was grown from seed to seed wholly in microgravity on the International Space Station. Arabidopsis plants were germinated, grown, and maintained inside a growth chamber prior to returning to Earth. Some of these seeds were used in a subsequent experiment to successfully produce a second (back-toback) generation of microgravity-grown Arabidopsis. In general, plant growth and development in microgravity proceeded similarly to those of the ground controls, which were grown in an identical cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 49 publications
3
48
0
Order By: Relevance
“…Other morphological alterations of the root, such as a skewed growth and an abnormal number of adventitious roots were also reported to occur in space-grown seedlings (Millar et al, 2011). Interestingly, a "seed-to-seed" experiment in space has shown that, even though the entire life cycle of plants can be achieved in real microgravity without serious apparent damages to the health and viability of daughter plants, noticeable changes in the shape of plant organs were identified (Link et al, 2014).…”
Section: Root Development: Gravimorphic Effectsmentioning
confidence: 99%
“…Other morphological alterations of the root, such as a skewed growth and an abnormal number of adventitious roots were also reported to occur in space-grown seedlings (Millar et al, 2011). Interestingly, a "seed-to-seed" experiment in space has shown that, even though the entire life cycle of plants can be achieved in real microgravity without serious apparent damages to the health and viability of daughter plants, noticeable changes in the shape of plant organs were identified (Link et al, 2014).…”
Section: Root Development: Gravimorphic Effectsmentioning
confidence: 99%
“…Based on previous studies, plants are able to grow and reproduce in outer space conditions Nevertheless, some abnormalities were observed, including chromosomal breakage, failures in seed production, nonviable embryos, and changes in gene expression (Link et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A RPM is a version of 3D clinostat, which continuously realizes random changes in the orientation relative to the gravity vector in a biological experiment (Borst et al ., 2009). The first experiment of Arabidopsis thaliana in microgravity was performed by Merkys and Laurinavicius (1983), they obtained some viable seeds, on the other hand several of seed contained nonviable embryos (reviewed in Link et al ., 2014). Simulated (micro)gravity is stressful for plants, and has an influence on plant growth, as well as on cellular and molecular responses such as cell cycle, embryogenesis, seeds, photosynthesis, gravitropic sensing/response, cell wall composition/properties, and changes of gene expression (Link et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant research in a space greenhouse [ Figure 7] has allowed the study of root zone substrates in space allowing scientists to improve predictions of how artificial soils will behave when irrigated both in space and on Earth in experimental forests [18].…”
Section: Ii5 Food and The Environmentmentioning
confidence: 99%